Effect of wrist orthoses on upper limb function, activities of daily living, and stress response - Hirata, Junya; Yoshimura, Manabu; Inoue, Keiko (Journal of Rehabilitation and Assistive Technologies Engineering, 2024)
Introduction This study examined the effects on upper limb function, activities of daily living, and stress responses when wearing a wrist orthosis made of padded fiberglass or thermoplastic and provided essential information for selecting an orthosis. Methods Thirty-one healthy adults performed two tests while not wearing a wrist orthosis, wearing a padded fiberglass wrist orthosis, and wearing a thermoplastic wrist orthosis. The Purdue Pegboard Test examined upper limb control. In the second test, the actions indicated by the Hand20 questionnaire were performed while wearing a wrist orthosis. An electrocardiogram was obtained before and after each test to identify any changes in sympathetic nervous system activity. Results The Purdue Pegboard Test scores were significantly higher when not wearing a wrist orthosis than when wearing wrist orthosis, and the Hand20 scores for all question were significantly lower. Thermoplastic wrist orthoses had fewer restrictions for upper limb function compared to padded fiberglass wrist orthoses, however activities of daily living were more limited. The low frequency/high frequency ratio and high frequency measures showed no significant differences. Conclusions Pegboard test scores and the Hand 20 scores suggest that a wrist orthosis causes restriction of upper limb function.